Crystal structure of an inulosucrase from Halalkalicoccusjeotgali B3T, a halophilic archaeal strain. (22nd April 2021) - Ghauri, Komal; Pijning, Tjaard; Munawar, Nayla; Ali, Hazrat; Ghauri, Muhammad A.; Anwar, Munir A.; Wallis, Russell
Abstract : Several archaea harbor genes that code for fructosyltransferase (FTF) enzymes. These enzymes have not been characterized yet at structure–function level, but are of extreme interest in view of their potential role in the synthesis of novel compounds for food, nutrition, and pharmaceutical applications. In this study, 3D structure of an inulin‐type fructan producing enzyme, inulosucrase (InuHj), from the archaeon Halalkalicoccus jeotgali was resolved in its apo form and with bound substrate (sucrose) molecule and first transglycosylation product (1‐kestose). This is the first crystal structure of an FTF from halophilic archaea. Its overall five‐bladed β‐propeller fold is conserved with previously reported FTFs, but also shows some unique features. The InuHj structure is closer to those of Gram‐negative bacteria, with exceptions such as residue E266, which is conserved in FTFs of Gram‐positive bacteria and has possible role in fructan polymer synthesis in these bacteria as compared to fructooligosaccharide (FOS) production by FTFs of Gram‐negative bacteria. Highly negative electrostatic surface potential of InuHj, due to a large amount of acidic residues, likely contributes to its halophilicity. The complex of InuHj with 1‐kestose indicates that the residues D287 in the 4B‐4C loop, Y330 in 4D‐5A, and D361 in the unique α2 helix may interact with longer FOSs and facilitate the binding of longer FOS chains during synthesis. The outcome of this work will provide targets for future structure–function studies of FTF enzymes, particularly those from archaea. Abstract : Crystal structures of an inulosucrase (InuHj) from archaeon Halalkalicoccus jeotgali in its apo form and complexed with sucrose and 1‐kestose were resolved for the first time. Important residues were identified that may interact with longer fructooligosaccharide (FOS) and facilitate the binding of longer FOS chains during synthesis. Highly negative electrostatic surface potential of InuHj, due to a large amount of acidic residues, likely contributes to its halophilicity.